Inteins—A Focus on the Biotechnological Applications of Splicing-Promoting Proteins - Miraula, Manfredi; Enculescu, Charmaine; Mitić, Natasa; Schenk, Gerhard (Scientific Research Publishing, 2015)
The main aim of this mini-review is to illustrate strategies and industrial applications based on inteins (INTErnal proteINS), which belong to a class of autocatalytic enzymes that are able to perform a catalytic reaction on a single substrate. However, since practical applications of inteins are strongly guided by a detailed understanding of their biological mechanisms and functions, the first part of this review will thus briefly discuss the physiological roles of inteins, describing what is currently known about their mechanisms of action. In the second part, specific biotechnological applications of inteins will be outlined (i.e. their use for (i) the purification of recombinant proteins, (ii) the cyclization of proteins and (iii) the production of seleno-proteins), paying attention to both potential strengths and weaknesses of this technology.
Keywords: Intein; Protein Purification; Tagged Protein; Cyclization; Selenoprotein